Prosocial behavior in a situation of moral choice: Theoretical approaches to research - N.A. Solovova; A.V. Kirpichev; M.A. Gagarina (Современная зарубежная психология)
Context and relevance. Despite the fact that publications on the problem of prosocial behavior are quite numerous, there are nevertheless disagreements regarding its structure, components and determinants. Objective. To determine the most effective theoretical model of prosocial behavior in conditions of moral choice, relevant for research in economic psychology. Hypothesis. In economic psychology research, a model that considers both social and individual norms will be the most promising for explaining prosocial behavior in a situation of moral choice. Methods and materials. We analyzed national and foreign articles in highly ranked journals that correspond to the research topic and were published mainly within the last three years. Results. A review of research on prosocial behavior, moral decision making, and models explaining their relationship is presented, including the Norm Activation Model, the Theory of Planned Behavior, and the Integrating Model. An analysis of approaches to the relationship between the concepts of «prosocial behavior» and «altruism» allowed us to conclude that altruism can act as one of the motives for prosocial behavior, along with egoism, collectivism, principlism, and reciprocity. The differences in the traditions of moral research in foreign and domestic psychology are presented and a definition of moral choice is proposed, as well as options for the relationship between prosocial behavior and moral choice. Conclusions. The most promising model for studying prosocial behavior in the context of moral choice is the model, integrating the Norm Activation Model and the Theory of Planned Behavior. It allows us to take into account both personal and social norms and their role in choosing the benefits for oneself and others.